Majapahit Heritage in the Cultural System of the Sultanate of Demak Bintara - Romdhoni, Ali; Che Noh, Noorsafuan Bin; Cholid, Nur; Hartatik, Endah Sri; Wasino, Wasino (History Department, Semarang State University and Historian Society of Indonesia, 2024)
Abstract: Although historical researchers do not doubt the identity of the Demak Bintara Sultanate as an Islamic kingdom, there are old cultural systems that continue to be used by generations of the Demak Bintara Sultanate. This article aims to study the legacy of Majapahit in the cultural system of the Demak Bintara Sultanate. The research method used in this article is historical, examining secondary sources on the history of Majapahit and Demak Bintara. The results of this study indicate the existence of a social and political system that prevailed when Majapahit still existed until the establishment of Demak Bintara. Majapahit and Demak Bintara operated a mandala political system, a pattern of relationships among kingdoms in a region with a large kingdom as the center. In addition, the pattern of relations between the clergy and rulers in the Majapahit and Demak Bintara eras shows similarities. The rulers maintained good relations with the clergy to gain political support and power. On the other hand, the kings provided various facilities to the clergy for educational needs and religious rituals. Majapahit and Demak Bintara also had an orientation as maritime kingdoms. These findings imply that the cultural heritage identities of Majapahit and Demak Bintara that can be found today are not necessarily different. This refutes some people's assumption that the Demak Bintara generation always purified any cultural heritage of Majapahit. Abstrak: Meskipun identitas Kesultanan Demak Bintara sebagai kerajaan Islam tidak diragukan oleh para peneliti sejarah, namun demikian terdapat sistem budaya lama yang terus digunakan oleh generasi Kesultanan Demak Bintara. Artikel ini bertujuan mengkaji warisan Majapahit dalam sistem budaya Kesultanan Demak Bintara. Metode penelitian yang digunakan dalam artikel ini adalah metode sejarah dengan mengkaji sumber-sumber sekunder tentang sejarah Majapahit dan Demak Bintara. Hasil kajian ini menunjukkan adanya sistem sosial dan politik yang berlaku pada masa Majapahit masih eksis sampai berdirinya Demak Bintara. Majapahit dan Demak Bintara menjalankan sistem politik mandala, yaitu pola hubungan antar kerajaan di satu wilayah dengan satu kerajaan besar sebagai pusatnya. Selain itu, pola hubungan antara para agamawan dan penguasa di era Majapahit dan Demak Bintara menunjukkan kesamaan. Para penguasa menjaga hubungan baik dengan kaum agamawan untuk mendapatkan dukungan politik dan kekuasaan. Di sisi lain, para raja memberikan berbagai fasilitas kepada agamawan untuk kebutuhan pendidikan dan ritual agama. Majapahit dan Demak Bintara juga memiliki orientasi sebagai kerajaan maritim. Implikasi dari temuan ini adalah identitas warisan budaya Majapahit dan Demak Bintara yang masih bisa dijumpai hari ini tidak selalu berbeda. Hal ini membantah anggapan sebagian orang bahwa setiap budaya warisan Majapahit selalu dibersihkan oleh generasi Demak Bintara.